Internet banking acceptance towards improving sustainability: a systematic literature review - Aziz, Khairi Azhar; Abdullah, Salfarina; A. Jabar, Marzanah; Nor, Rozi Nor Haizan; Jusoh, Yusmadi Yah (IEEE, 2023)
Internet banking is nowadays an important platform for taking care of financial matters. Researchers have introduced the acceptance of internet banking, which allows users to fulfil their obligations without visiting a counter. Nevertheless, the lack of sustainability of internet banking acceptance can systematically present the current research. The proposed study proposes a systematic literature review on internet banking acceptance to overcome this limitation. This systematic literature review (SLR) will help practitioners to draw on the existing literature and propose new solutions based on the existing internet banking adoption. The results of this paper can help future researchers from industry and academia by providing a guide for practitioners to identify approaches to successfully implement internet banking acceptance.